Semaphorin 4D inhibits neutrophil activation and is involved in the pathogenesis of neutrophil-mediated autoimmune vasculitis. Issue 8 (17th April 2017) - Nishide, Masayuki; Nojima, Satoshi; Ito, Daisuke; Takamatsu, Hyota; Koyama, Shohei; Kang, Sujin; Kimura, Tetsuya; Morimoto, Keiko; Hosokawa, Takashi; Hayama, Yoshitomo; Kinehara, Yuhei; Kato, Yasuhiro; et al.
Abstract : Objectives: Inappropriate activation of neutrophils plays a pathological role in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). The aim of this study was to investigate the functions of semaphorin 4D (SEMA4D) in regulation of neutrophil activation, and its involvement in AAV pathogenesis. Methods: Serum levels of soluble SEMA4D were evaluated by ELISA. Blood cell-surface expression of membrane SEMA4D was evaluated by flow cytometry. To determine the functional interactions between neutrophil membrane SEMA4D and endothelial plexin B2, wild-type and SEMA4D −/− mice neutrophils were cultured with an endothelial cell line (MS1) stained with SYTOX green, and subjected to neutrophil extracellular trap (NET) formation assays. The efficacy of treating human neutrophils with recombinant plexin B2 was assessed by measuring the kinetic oxidative burst and NET formation assays. Results: Serum levels of soluble SEMA4D were elevated in patients with AAV and correlated with disease activity scores. Cell-surface expression of SEMA4D was downregulated in neutrophils from patients with AAV, a consequence of proteolytic cleavage of membrane SEMA4D. Soluble SEMA4D exerted pro-inflammatory effects on endothelial cells. Membranous SEMA4D on neutrophils bound to plexin B2 on endothelial cells, and this interaction decreased NET formation. Recombinant plexin B2 suppressed neutrophil Rac1 activation through SEMA4D's intracellular domain, and inhibited pathogen-induced or ANCA-induced oxidative burst and NET formation. Conclusions: Neutrophil surface SEMA4D functions as a negative regulator of neutrophil activation. Proteolytic cleavage of SEMA4D as observed in patients with AAV may amplify neutrophil-mediated inflammatory responses. SEMA4D is a promising biomarker and potential therapeutic target for AAV.